Longitudinal study of hearing preservation and electrocochleography after cochlear implantation in adults - Marianne Schleich; John J. Galvin, III; Fabrice Micaletti; David Bakhos (Brazilian Journal of Otorhinolaryngology)
Objectives: Electrocochleography (ECOG) is a composite objective measure of the cochlea and the cochlear nerve responses. The objectives of this study were to investigate the evolution of ECOG after cochlear implantation and compare them with audiometric thresholds over a 12-month period. Methods: A prospective monocentric study was conducted in Advanced Bionics cochlear implant recipients. Audiometric thresholds were recorded preoperatively and at 1-, 3-, 6-, and 12-months post cochlear implantation; ECOGs were recorded perioperatively after the electrode array insertion and at 1-, 3-, 6-, and 12-months post cochlear implantation. Cochlear Microphonic (CM) responses were measured by an apical electrode of the cochlear implant. Postoperative behavioral and ECOG thresholds were compared using Pearson correlation analyses. Results: A total of 17 patients were included. At 1-year, residual hearing (≤90 dB HL at 500 Hz) was preserved for 4 out of 17 patients. Significant correlations were observed between perioperative ECOG and preoperative audiometric thresholds (p = 0.008), and between ECOG and audiometric thresholds at 3-months postoperative (p = 0.002). Conclusion: ECOG can reflect changes in cochlear responses during and after implantation and may help to predict deterioration of residual hearing. Level of evidence: Level 3.